Coral reef restoration for coastal protection: Crafting technical and financial solutions. (15th May 2022) - Brathwaite, Angelique; Clua, Eric; Roach, Ramon; Pascal, Nicolas
Abstract: Coastal erosion, aggravated by coral reef mortality is a major issue for Small Island Developing States. Traditionally gray infrastructure, financed by public budgets has been used to combat beach loss. We examined if three Nature-based Solutions (NbS): (i) coral restoration (green) (ii) restoration + limestone (hybrid) and (iii) restoration + 3D printed concrete (hybrid) could deliver positive outcomes for coastal protection and further incentivize cost sharing for reef conservation, with private beneficiaries. We modelled the impact of restoration on wave attenuation at two reefs off Barbados and simulated up-front and maintenance costs over a 25-year period. All solutions provide additionality when compared to gray infrastructure, especially in mitigating against Sea Level Rise. Restoration was the least costly with the highest risk of failure. The hybrid solutions, were less risky than the green as they provided immediate wave attenuation, alongside complementary services such as increased attractiveness due to the presence of reef fish. Their costs were however between +80% and +450% higher than gray solutions. While this might initially deter the use of NbS, blended finance and in some cases, Payments for Ecosystem Services, could provide options for governments and private beneficiaries to share costs, with ultimately greater benefits for themselves and coral reefs. Highlights: Reef restoration can assist in mitigating coastal erosion for coastal protection. Hybrid solutions can be costlier than gray infrastructure, but provide additionality. Blended finance & PES allow for cost sharing with beneficiaries.